2019
DOI: 10.1016/j.healun.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes with ambulatory advanced heart failure from the Medical Arm of Mechanically Assisted Circulatory Support (MedaMACS) Registry

Abstract: BACKGROUND: The outlook for ambulatory patients with advanced heart failure (HF) and the appropriate timing for left ventricular assist device (LVAD) or transplant remain uncertain. The aim of this study was to better understand disease trajectory and rates of progression to subsequent LVAD therapy and transplant in ambulatory advanced HF. METHODS: Patients with advanced HF who were New York Heart Association (NYHA) Class III or IV and Interagency Registry for Mechanically Assisted Circulatory Support (INTERMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 19 publications
0
46
1
Order By: Relevance
“…An analysis of the previously described Meda-MACS registry matched with Profiles 4 to 7 patients with LVADs from the INTERMACS registry indicated that survival was similar for medical, and LVAD therapy in the overall cohort, which included the lower severity Profiles 6 and 7, but survival was better with LVAD therapy among patients in Profiles 4 and 5. 19 The current findings are an essential extension with larger samples comprising more Profile 6 and 7 patients. These findings demonstrated that Profiles 6 and 7 have distinct and clinically relevant trajectories and better map the transition from Stage C to D HF.…”
Section: Figurementioning
confidence: 65%
“…An analysis of the previously described Meda-MACS registry matched with Profiles 4 to 7 patients with LVADs from the INTERMACS registry indicated that survival was similar for medical, and LVAD therapy in the overall cohort, which included the lower severity Profiles 6 and 7, but survival was better with LVAD therapy among patients in Profiles 4 and 5. 19 The current findings are an essential extension with larger samples comprising more Profile 6 and 7 patients. These findings demonstrated that Profiles 6 and 7 have distinct and clinically relevant trajectories and better map the transition from Stage C to D HF.…”
Section: Figurementioning
confidence: 65%
“…REVIVAL subjects had much greater functional capacity (mean 6-minute walk distance, 336 vs. 196 meters), greater overall generic HRQOL (EQ visual analogue scale, 65 vs. 56), and better HF-related QOL (Kansas City Cardiomyopathy Questionnaire overall summary score, 64 vs. 51) than subjects in the MedaMACS Pilot. 12 Freedom from death, heart transplant (UNOS 1A or 1B for REVIVAL, any transplant for both MedaMACS studies and the optimal medical management arm of ROAD-MAP), or durable MCS at 1-year for each cohort are consistent with these differences in enrollment criteria and baseline characteristics: 76% for REVIVAL, »63% for the MedaMACS Pilot, 63% for the optimal medical management arm of ROADMAP, and 47% for the MedaMACS Screening Pilot. Thus, REVIVAL represents a less advanced chronic systolic HF cohort that is centered beneath the current threshold at which the advanced HF community believes surgical intervention with a transplant or durable MCS is generally indicated.…”
Section: Figurementioning
confidence: 72%
“…Serial assessments of hospitalizations, medication changes, functional capacity, quality of life, health utility, depression, anxiety, willingness to receive VAD and other end-stage disease life-sustaining Figure 1A, 1B, and 1C from the published study. 12 Urgent transplants were those categorized as UNOS 1A or 1B at the time of transplant.…”
Section: Figurementioning
confidence: 99%
“…MCS may optimize left sided hemodynamics, though this will in part be reliant on the adequacy of RV function. This raises the question whether the current patient should have undergone LVAD placement at the time of his index hospitalization, prior to the development of recalcitrant RV failure, given the very poor prognosis in such patients . In summary, regardless of the inotrope or MCS used, the outcomes in advanced HFrEF are often dictated by the right heart and renal function.…”
Section: Casementioning
confidence: 99%